First report of Furcraea foetida (Agavaceae) for Argentina - Giraldo-Cañas, Diego (2023)
Furcraea foetida (L.) Haw., a native species from tropical America, is recorded for the first time for Argentina. Its description, photographs, vernacular names, uses, some morphological and ecological analyses, are given.